Biodegradable polyesters - Fakirov, Stoyko (Wiley-VCH, 2015)
Collating otherwise hard-to-get and recently acquired knowledge in one work, this is a comprehensive reference on the synthesis, properties, characterization, and applications of this eco-friendly class of plastics. A group of internationally renowned researchers offer their first-hand experience and knowledge, dealing exclusively with those biodegradable polyesters that have become increasingly important over the past two decades due to environmental concerns on the one hand and newly-devised applications in the biomedical field on the other. The result is an unparalleled overview for the.- Resumé vydavatel
Keywords: polyestery; biodegradovatelné polymery; polyesters; biodegradable polymers; elektronické knihy; kolektivní monografie; electronic books; collective monographs